Significant differences in cesarean section rates between a private and a public hospital in Brazil Diferença notável nas taxas de parto cesariano em hospital público e hospital privado no Brasil - Sueli de Almeida; Heloisa Bettiol; Marco Antonio Barbieri; Antônio Augusto Moura da Silva; Valdinar Sousa Ribeiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This paper evaluates the association of maternal variables and of variables related to prenatal and delivery care with cesarean sections at a public and at a private maternity. A retrospective cross-sectional study was performed at a public maternity clinic (2,889 deliveries) and at a private maternity clinic (2,911 deliveries) in the city of Ribeirão Preto, São Paulo State, Brazil. The prevalence of cesarean sections was 18.9% at the public maternity clinic and 84.3% at the private one. The factors associated with cesarean sections at both hospitals were: mothers from other cities, aged > 25 years and with hypertension. Having more than one child was a protective factor. At the public hospital, cesarean sections were more frequent on Wednesdays and from 12:00 to 23:59 hours of any day of the week, whereas at the private hospital they occurred on any day, though were less common on Sundays, and at any time except in the early morning. At the private hospital, cesarean sections were more frequent when performed by the doctor who had provided the prenatal care. Non-medical factors were more associated with cesarean sections in the private maternity clinic than biological or clinical factors related to pregnancy. Este artigo avalia a associação de variáveis maternas e aquelas relacionadas ao cuidado pré-natal e ao parto com a ocorrência de cesáreas em um hospital público e em um hospital privado. Um estudo de corte transversal, retrospectivo, foi desenvolvido em uma maternidade pública (2.889 partos) e em uma maternidade privada (2.911 partos) em Ribeirão Preto, São Paulo, Brasil. A prevalência de cesárea foi 18,9% e 84,3%, respectivamente, na maternidade pública e na particular. Os fatores associados ao parto cesariano nos dois hospitais foram: mães procedentes de outras cidades, com idade > 25 anos e hipertensas. Ter mais de um filho foi fator protetor. No hospital público, a cesárea foi mais freqüente às quartas-feiras e das 12h00min às 23h59min de qualquer dia da semana, enquanto no hospital privado prevaleceram em qualquer dia, exceto aos domingos, e em qualquer horário, exceto de madrugada. Neste hospital, a cesárea foi mais freqüente quando realizada pelo médico que acompanhou o pré-natal. Fatores não médicos foram mais associados com os partos operatórios na maternidade privada do que fatores biológicos ou clínicos das gestantes.